The gospel of the Lord : how the early church wrote the story of Jesus - Bird, Michael F. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2014)
In this book, through a distinctive evangelical and critical approach, Michael Bird explores the historical development of the four canonical Gospels. He shows how the memories and faith of the earliest believers formed the Gospel accounts of Jesus that got written and, in turn, how these accounts further shaped the early church. Bird's study clarifies the often confusing debates over the origins of the canonical Gospels. Bird navigates recent concerns and research as he builds an informed case for how the early Christ followers wrote and spread the story of Jesus — the story by which they believed they were called to live. The Gospel of the Lord is ideal for students or anyone who wants to know the story behind the four Gospels.
Introduction: From Jesus to Gospels -- The Purpose and Preservation of the Jesus Tradition -- The Formation of the Jesus Tradition -- The Literary Genetics of the Gospels: The Synoptic Problem and Johannine Question -- The Genre and Goal of the Gospels: What Is a Gospel and Why Write One? -- The Fourfold Gospel of Jesus Christ: Why Four Gospels?
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- Historicity; Jesus Christ -- Biography -- Sources; Bible. -- Authorship